A systematic DFT study of structure and electronic properties of titanium dioxide - Asma Marzouk (1980166) (2024)
DFT functionals are of paramount importance for an accurate electronic and structural description of transition metal systems. In this work, a systematic analysis using some well‐known and commonly used DFT functionals is performed. A comparison of the structural and energetic parameters calculated with the available experimental data is made in order to find the adequate functional for an accurate description of the TiO2 bulk and surface of both anatase and rutile structures. In the absence of experimental data on the surface energy, the theoretical predictions obtained using the high‐accuracy HSE06 functional were used as a reference to compare against the surface energy values calculated with the other DFT functionals. A clear improvement in the electronic description of both anatase and rutile was observed by introducing the Hubbard U correction term to PBE, PW91, and OptPBE functionals. The OptPBE‐U4 functional was found to offer a good compromise between accurately describing the structural and electronic properties of titania. Other Information Published in: Journal of Computational Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jcc.27376